Exploration of Alkaliphilic Actinomycetes for Amylase Production from Agroindustrial Waste - Vidhale NN; Pundkar VM (International Journal of Life Sciences, 2016)
Saline soil possessing high pH value (above 8.0) predominates alkaliphilic actinomycetes (Singh S et al., 2010), which can be explored for the production of amylase from agroindustrial waste as substrate using solid state fermentation. In this study six types of agroindustrial waste such as wheat bran, rice bran, Dal mil waste, oil mil waste, vegetable waste and molasses were employed. Solid state fermentation (SSF) was carried out at various moisture content (10 to 35%) at 37˚ c. results indicates that alkaliphilic Actinomycetes from saline soil of vidarbha region produced maximum amylase in vegetable waste (4.45mg/ml) in presence of 30 % moisture after 96 hrs, followed by oil mil waste (4.5mg/ml) in presence of 25%moisture after 120hrs, wheat bran and rice bran (3.9mg/ml) at 25%moisture content after 120hrs and 96hrs respectively. Dal mil waste was found to produce 3.5mg/ml amylase in presence of 25% moisture after 96hrs and molasses showed very least production of amylase (2mg/ml) after 144hrs. Hence it indicates that agroindustrial wastes are good source for the production of amylase using alkaliphilic Actinomycetes.